Pengaruh Keselamatan Kerja dan Kesehatan Kerja terhadap Kinerja Pegawai Seksi Penanggulangan Kebakaran dan Penyelamatan pada Dinas Pemadam Kebakaran Kota XYZ - Anggi Novia Rahma; Mochamad Vrans Romi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of occupational safety and health on the performance of employees in the Fire and Rescue Section at the XYZ City Fire Department. The research method used was a quantitative approach with descriptive and associative methods. Data collection techniques included observation, documentation, and questionnaires, and data analysis using multiple linear regression. The results showed that occupational safety and health partially had a positive and significant effect on employee performance, and simultaneously, both variables also had a significant effect on employee performance, contributing 55%. The conclusion of this study is that improving occupational safety and health can improve employee performance. Therefore, it is necessary to provide a safe work environment, complete personal protective equipment, and optimal occupational health maintenance to support better employee performance. Keywords: Occupational Safety, Occupational Health, Employee Performance, Fire Department